HXE 228 - English Poetry June 2016 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 2016)
Please check that this examination paper consists of THREE pages of printed material before you begin the examination. Answer FOUR questions. Answer TWO questions from Section A and TWO questions from Section B.